2016
DOI: 10.1038/srep27406
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ordering reduces electric susceptibility of liquids confined to graphene slit pores

Abstract: The behaviours of a range of polar and non-polar organic liquids (acetone, ethanol, methanol, N-methyl-2-pyrrolidone (NMP), carbon tetrachloride and water) confined to 2D graphene nanochannels with thicknesses in the range of 4.5 Å to 40 Å were studied using classical molecular dynamics and hybrid density functional theory. All liquids were found to organise spontaneously into ordered layers parallel to the confining surfaces, with those containing polar molecules having their electric dipoles aligned parallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…As depicted in Figure a–d, for all the fluids considered, compared to the bulk, the in-plane dipole–dipole correlation, h Δ ( r ) (see the Methods section for definition) is enhanced, showing the tendency of the dipoles to lay parallel to the graphene surface. Such a preferred orientation was reported for polar liquids on graphene . This preferred orientation can be understood by analyzing the in-plane dipole–dipole electrostatic energy of the interfacial layer, which can be written as where h D represents the angular dependence of the dipole–dipole interaction energy (see the Methods section for mathematical definition), r ∥ is the in-plane separation distance between the dipoles, L IFL is the width of the interfacial layer, and ρ IFL is the density of the molecules in the interfacial layer.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…As depicted in Figure a–d, for all the fluids considered, compared to the bulk, the in-plane dipole–dipole correlation, h Δ ( r ) (see the Methods section for definition) is enhanced, showing the tendency of the dipoles to lay parallel to the graphene surface. Such a preferred orientation was reported for polar liquids on graphene . This preferred orientation can be understood by analyzing the in-plane dipole–dipole electrostatic energy of the interfacial layer, which can be written as where h D represents the angular dependence of the dipole–dipole interaction energy (see the Methods section for mathematical definition), r ∥ is the in-plane separation distance between the dipoles, L IFL is the width of the interfacial layer, and ρ IFL is the density of the molecules in the interfacial layer.…”
Section: Resultsmentioning
confidence: 74%
“…50 However, our results indicate that not only protic fluids such as water or methanol (hydrogen-bonding fluids) but also aprotic fluids exhibit a low out-of-plane dielectric permittivity under confinement, suggesting that the underlying mechanism for the reduction in permittivity is not just due to the hydrogen bond network effect in the interfacial layer (IFL). Since the main contribution to the static dielectric permittivity of polar fluids is the orientational polarizability (compared to the electronic polarizability), 51 and the dominant term is the dipole polarization, we investigate the in-plane dipole orientational correlations in the first fluid density layer (interfacial layer) adjacent to the wall (see Supplementary Figure S5). As depicted in Figure 3a− d, for all the fluids considered, compared to the bulk, the inplane dipole−dipole correlation, h Δ (r) (see the Methods section for definition) is enhanced, showing the tendency of the dipoles to lay parallel to the graphene surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model for the ionic liquid can be generalised with ease to incorporate non-constant permittivities and diffusivities; molecular dynamics and mean-field simulations have shown that confinement can cause significant variations in these quantities [Kondrat et al, 2014, Terrones et al, 2016. Relevant DDFT studies include the work of Qing et al [2020] incorporating density-dependent permittivities, and the theoretical investigation of packing fraction-dependent diffusivities by Stopper et al [2018].…”
Section: Discussionmentioning
confidence: 99%
“…Particular attention is focused on the study of the effect of external fields (electric, magnetic, ultrasonic, etc.) on the crystallization of confined water [29][30][31][32]. The crystallization of water in an applied electric field -electrocrystallization -is a key phenomenon for such processes as the formation of atmospheric precipitation, formation and growth of ice on the wings of aircraft, and cryoconservation of biological materials [33,34].The aim of this work is to study the effect of the strength and direction of a uniform electric field on the process of crystallization of spatially confined supercooled water.…”
mentioning
confidence: 99%